2020
DOI: 10.1101/2020.05.25.111690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Loading of Human Engineered Heart Tissue Enhances Contractile Function and Drives Desmosome-linked Disease Phenotype

Abstract: The role mechanical forces play in shaping the structure and function of the heart is critical to understanding heart formation and the etiology of disease but is challenging to study in patients. Engineered heart tissues (EHTs) incorporating human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes have the potential to provide insight into these adaptive and maladaptive changes in the heart. However, most EHT systems are unable to model both preload (stretch during chamber filling) and afterload (pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 85 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…However, it is unclear if modeling preload and afterload enables disease manifestation, or if it is the improved maturation in the system that brings about the defects observed. 40 There are other approaches that are suitable for modeling afterload. A key parameter that can be manipulated with respect to mechanical loading is substrate stiffness.…”
Section: Mechanical Loadingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is unclear if modeling preload and afterload enables disease manifestation, or if it is the improved maturation in the system that brings about the defects observed. 40 There are other approaches that are suitable for modeling afterload. A key parameter that can be manipulated with respect to mechanical loading is substrate stiffness.…”
Section: Mechanical Loadingmentioning
confidence: 99%
“…While most heart‐on‐a‐chip setups do not replicate both preload (pressure from ventricular filling) and afterload (pressure the ventricle must work against to pump blood) on cardiac microtissues, a recent study has used a bent silicone rod to mimic aspects of both preload and afterload, while also enabling force measurements by bending of the same rod (Figure 1D). 40 This system was shown to improve the maturation of hiPSC‐CMs, demonstrated by gene expression and improved conduction velocity. The application of load also resulted increased fidelity of sarcomeric alignment compared with having constrained rods (no load).…”
Section: Disease Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac spheroids and organoids provide an ability to place hiPSC-CMs in a 3D structure, and this clearly provides some advantages, however the structure and function still recapitulates the embryonic state at best 20 . Engineered heart tissues (EHTs) have been developed to better recreate the 3D structure and function of the heart at the tissue and organ scale, leading to more physiologically data-rich assays [21][22][23][24][25][26][27][28][29][30] . Current 3D fabrication approaches for hiPSC-CMs through molding of cell-laden hydrogels, seeding on fiber-based scaffolds and 3D bioprinting have been effective in creating contractile cardiac tissues in a dish.…”
Section: Introductionmentioning
confidence: 99%
“…FRESH™ 3D bioprinting works by extruding cell-laden bioinks within a gelatin microparticle support bath that provides mechanical support to the bioink while it gels and then can be non-destructively removed by melting at 37°C 31 . We have previously demonstrated that FRESH™ 3D bioprinting can be used to engineer cardiac tissues in a range of complex 3D structures such as ventricle-like constructs and heart tubes with advanced functionality 29,30 . To expand upon this, we created a process that enables EHTs to be FRESH™ 3D printed around custom-designed tissue fixtures within 24-well plates and then performed structural, functional, and pharmacologic assays to demonstrate platform capabilities.…”
Section: Introductionmentioning
confidence: 99%